PENGUATAN LITERASI TEKNOLOGI MELALUI PEMBELAJARAN PRAKTIK INTERNET OF THINGS (IoT) PADA INDUSTRI GALANGAN KAPAL PT. VESINTER INDONESIA - Richmayati, Maya; lLutfiah, Umahatul; Sabri, Sabri; Mulyadi, Mulyadi; Sandra, Elminaliya (ASOSIASI IDEBAHASA KEPRI, 2025)
Internet of Things (IoT) is one form of organizational environmental strategy to improve business performance. so that with an integrated system, coordination between departments will be right on target. In this practical learning, the focus is on human resource management (HR), especially payroll administration, employee attendance systems, and BPJS management, and focuses on the digitalization system. The manual system is still used at PT. Vesinter Indonesia, especially raw data management and has not implemented an integrated information system, which causes various obstacles, such as time inefficiency, risk of error, and weak employee data protection. Therefore, it is important to provide an understanding of how important the IoT system is to companies engaged in large businesses. A good payroll system will certainly avoid fraud in the company, but if the opposite is true, there will certainly be deviations. PT Vesinter Indonesia is advised to implement a digital-based payroll system (payroll software) that is integrated with attendance and BPJS data. With this system, the process of calculating salaries, overtime, and deductions will be more accurate, faster, and minimize errors. Companies need to develop a personnel information system (Human Resource Information System) that can store employee data centrally and securely. This system will facilitate the recording of work history, contracts, performance evaluations, and BPJS reporting automatically. To support digitalization, companies need to provide regular training to HRD staff so that they can understand and operate digital systems effectively.